A CLOSER LOOK AT A PATH DOMINATION NUMBER IN GRID GRAPHS - Casinillo, Leomarich F (Journal of Fundamental Mathematics and Applications (JFMA), 2023)
This article exposes the combinatorial formula that determines the pathdomination number in a grid graph and discusses some of its properties. Seven propertiesare derived regarding the path domination number of grid graphs. Furthermore, some additional properties as direct consequences of the derived main properties are alsodiscussed.